Eosinophilic Colitis in Recurrent Sigmoid Volvulus. Issue 8 (25th August 2021) - Zucker, Kelly; Pradhan, Faruq; Gomez, Adam; Nanda, Rakesh
ABSTRACT: Eosinophilic colitis (EC) falls along the spectrum of a series of inflammatory gastrointestinal disorders in which eosinophils infiltrate the gut without known tissue eosinophilia. Eosinophilic gastrointestinal disorders include eosinophilic esophagitis, eosinophilic gastritis, and the least common EC. The presentation of EC is extremely variable in mucosal, submucosal, and transmural inflammation. We present a case of recurrent volvulus with histologic findings of eosinophilia.